Treating Diabetes Utilizing a Low Carbohydrate Ketogenic Diet and Intermittent Fasting Without Significant Weight Loss: A Case Report - Gavidia, Kristen; Kalayjian, Tro (Frontiers in Nutrition, 2021)
Prediabetes and diabetes are a leading cause of morbidity and mortality in the United States and is growing in prevalence over the past 50 years to 45% of the population. Current guidelines from the ADA recommends focus on energy balance, portion sizes and weight loss while cautioning that no ideal macronutrient composition has been determined. The guidelines also do not recommend intermittent fasting. In contrast, we report 3 cases of a substantial reduction in A1C without clinically significant weight loss using a unique, patient-centered program that utilizes low carbohydrate diets with intermittent fasting. These results call into question the role of weight reduction in the management of diabetes while highlighting the unique importance of carbohydrate restriction and intermittent fasting. Here, we demonstrate a case series of three patients with a substantial reduction in A1C, and significantly reducing the need for pharmacotherapy without clinically significant weight loss. Although anecdotal, these results call into question the ADA’s emphasis on weight reduction and reduction of energy intake for the management of diabetes.